ANALISIS PENGARUH PROMOSI PENJUALAN, PENATAAN PRODUK DAN SUASANA MALL TERHADAP PEMBELIAN TIDAK TERENCANA (STUDI KASUS PADA RAMAYANA DEPARTEMENT STORE YOGYAKARTA) - Wuri Plangi Ayatina; Saptaningsih Sumarmi (Universitas Ahmad Dahlan, 2020)
This study aims to analysis determine the effect of sales promotion, display product, and store atmosphere on impulse buying at the Ramayana Department Store Yogyakarta. This research was conducted at the Ramayana Department Store Yogyakarta in November 2018 until June 2019. This research was a quantitative study with 80 respondents. Data collection techniques is done by questionnaires and observation. The analysis technique used in this study uses multiple linear regression analysis. The results of this study concluded that sales promotion, display product, and store atmosphere has a positive and sign effect on impulse buying through partial testing and simultaneous testing.